Factors Influencing Online Academic Performance Among University Students - Ng, Hee Song; Kuek, Thiam Yong; Chen, Kah Huan; Chang, Jia Hao; Chee, Yu Ping; Chen, Li Jun; Pramana, I Made Gede Andita; Indrayana, Andy Ramadhan; Singh, Ayushi; Zirape, Saurabh (Asia Pacific Journal of Management and Education (APJME), 2023)
In recent years, the COVID-19 pandemic has made a significant impact on education around the world. Nevertheless, the governments of these nations have discovered a way to try to alleviate the education crisis during the pandemic by offering online academic classes. Students can continue to study without interfering with their future courses, and they'll not underestimate their studies since they have been isolated at home for a long time. The purpose of this research is to look into the factors that influence online academic performance among university students. Furthermore, the aim of the research is to investigate the link between student willingness, motivation, academic staff responsibilities, course design and content, perceived usefulness, ease of use, and university guidance. A total of 155 university students had been picked to take part in this research via â€œGoogle Formâ€.